Wireless bluetooth-based SIPESUT (Body Temperature Monitoring System) prototype - Agatha Puteri Vitria Wahyuningsih; Giner Maslebu; Andreas Setiawan (Journal of Science & Science Education, 2021)
Human body temperature is a very important parameter in monitoring health conditions. The differences in temperature can occur due to routine or the occurrence of health problems. Furthermore, many diseases are related to human body temperature and require monitoring. This study proposes the development of health technology for a wireless body temperature monitoring system. The results of the test show that the prototype system has succeeded in sending measurement data to the computer and Android systems. The calibration results also show conformity with standard measuring instruments.